Selecting a systems development approach for supplying computer based support for decision makers: a model and its validation by the Delphi technique - Archer, Norman P.; Dececchi, T.; McMaster University, Faculty of Business (My University, 1990)
This paper reports on part of a larger research project to develop a model which would aid in selecting the best systems development approach for supplying a decision maker with a computer based support system. The hierarchical model which has been developed includes a "top" level which describes situations in terms of four factors or meta-constructs; User Participation in the Decision Making Process, Problem Space Complexity, Resource Availability and Organizational Context. The "lower level" of the model describes each factor in terms of attributes. The first phase of the validation of the model is discussed including validation of the model structure and content by means of a Delphi study. A normative group technique was chosen since it was considered necessary to obtain expert consensus on both the factors and the attributes that defined them. The satisfactory validation results indicate that the model can be a useful aid for describing different situations where computer based support systems may need to be developed.
33 leaves ; Includes bibliographical references (leaves 23-28). ; "June, 1990".
Keywords: Business; Business; Delphi method Technological forecasting Decision making > Mathematical models